2000
DOI: 10.1159/000010293
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcome of Pregnancies Complicated by Diabetes and by Maternal Daily Hyperglycemia Not Related to Diabetes

Abstract: We analyzed the perinatal outcome of 1,086 pregnancies classified according to the response to the 3-hour 100-gram glucose tolerance test and the diurnal glycemic profile into the Rudge groups corresponding to control pregnant women, class A gestational diabetic women, class A/B to FRH pregnant women and women with daily hyperglycemia. Despite treatment, the diabetic pregnant women and those with daily hyperglycemia presented higher mean blood glucose levels compared to controls (76.6 ± 10.2 mg/dl). The pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0
29

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 8 publications
3
85
0
29
Order By: Relevance
“…A mãe é alertada sobre uma condição que pode afetar sua saúde no futuro e os riscos fetais, associados à tolerância diminuída à glicose, podem ser prevenidos ou minimizados com o tratamento adequado. 3,4 Não existe, contudo, consenso a respeito dos métodos de rastreamento e diagnóstico do diabete gestacional. Isso porque essa afecção específica aglutina uma série de distúrbios relacionados à ação e à secreção de insulina e seu simples reconhecimento, pela primeira vez na gravidez, não descarta a possibilidade de sua pré-existência.…”
Section: Introductionunclassified
“…A mãe é alertada sobre uma condição que pode afetar sua saúde no futuro e os riscos fetais, associados à tolerância diminuída à glicose, podem ser prevenidos ou minimizados com o tratamento adequado. 3,4 Não existe, contudo, consenso a respeito dos métodos de rastreamento e diagnóstico do diabete gestacional. Isso porque essa afecção específica aglutina uma série de distúrbios relacionados à ação e à secreção de insulina e seu simples reconhecimento, pela primeira vez na gravidez, não descarta a possibilidade de sua pré-existência.…”
Section: Introductionunclassified
“…Se houver uma forte suspeita de diabetes na gestação atual -crescimento fetal exagerado, presença de polidrâmnio, ou a presença de vários fatores de risco -pode-se repetir algum dos testes para a detecção do diabetes gestacional: uma nova glicemia de jejum, o teste de tolerância de 75g ou o perfil glicêmico (7).…”
Section: Rastreamento Do Diabetes Gestacionalunclassified
“…This event is energy-dependent and detected by terminal transferase-mediated in situ end labeling (TUNEL) (Kim et al 2006). Investigations with animal models have also shown that in streptozotocin-induced diabetic rats, placental growth is markedly altered, exhibiting a notable decrease in apoptotic and proliferation indexes (Rudge et al 2000). Proliferating cell nuclear antigen (PCNA) protein is one of the central molecules responsible for decisions of life and death of the cell.…”
Section: Introductionmentioning
confidence: 99%